1995
DOI: 10.1111/j.1541-1338.1995.tb00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Election Day Registration on Voter Turnout: A Quasi‐experimental Analysis

Abstract: Election day registration is among the solutions suggested for remedying low voter turnout in the United States. This analysis uses a quasi-experimental time-series design to test the hypothesis that states adopting election day registration increase voter turnout in comparison to states that do not reform their election procedures. The similarities in the time series of voter turnout in the experimental and control states suggest that observed changes in states adopting election day registration resulted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Interestingly, Smolka's (1977) original case study of the effects of EDR on turnout in Minnesota and Wisconsin estimated that the introduction of EDR had an impact on turnout of no more than two percentage points. King andWambeam's (1995/1996) later study found a much larger seven percentage point increase in statewide voter turnout in Wisconsin as a result of EDR, but no corresponding increase in Minnesota or Maine. 2.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, Smolka's (1977) original case study of the effects of EDR on turnout in Minnesota and Wisconsin estimated that the introduction of EDR had an impact on turnout of no more than two percentage points. King andWambeam's (1995/1996) later study found a much larger seven percentage point increase in statewide voter turnout in Wisconsin as a result of EDR, but no corresponding increase in Minnesota or Maine. 2.…”
Section: Discussionmentioning
confidence: 93%
“…The results are especially consistent for the three early adopters, Maine, Minnesota, and Wisconsin. See, for example, Fenster (1994), King and Wambeam (1995), Knack and White (2000), Knack (2001), Neiheisel and Burden (2012), Springer (2014). The data from 1920 to 2000 are from Springer (2014).…”
Section: Empirical Examplementioning
confidence: 99%
“…22See, for example, Fenster (1994), King and Wambeam (1995), Knack and White (2000), Knack (2001), Neiheisel and Burden (2012), Springer (2014). …”
mentioning
confidence: 99%
“…When pooled cross-sections fail to (statistically) control for each state's unique history and qualities, this design also risks inadvertently ascribing preexisting state characteristics (e.g., high turnout) to other variables. Third, cross-sectional or longitudinal aggregate studies using aggregate data (e.g., Fleury, 1992;Fenster, 1994;Rhine, 1995;Knack, 1995;King and Wambeam, 1996;Franklin and Grier, 1997) are sharply limited in their capacity to control for citizens' individual characteristics known to influence turnout (e.g., education, income) without suffering from an ecological fallacy.…”
mentioning
confidence: 99%